Quantum Radiation Properties of General Nonstationary Black Hole - T. Ibungochouba Singh (Advances in High Energy Physics)
Using the generalized tortoise coordinate transformations the quantum radiation properties of Klein-Gordon scalar particles, Maxwell’s electromagnetic field equations, and Dirac equations are investigated in general nonstationary black hole. The locations of the event horizon and the Hawking temperature depend on both time and angles. A new extra coupling effect is observed in the thermal radiation spectrum of Maxwell’s equations and Dirac equations which is absent in the thermal radiation spectrum of scalar particles. We also observe that the chemical potential derived from scalar particles is equal to the highest energy of the negative-energy state of the scalar particle in the nonthermal radiation in general nonstationary black hole. Applying generalized tortoise coordinate transformation a constant term ξ is produced in the expression of thermal radiation in general nonstationary black hole. It indicates that generalized tortoise coordinate transformation is more accurate and reliable in the study of thermal radiation of black hole.